Fostering Empathy and Courage Through an Anti-Bullying Program in Karangtengah Village - Sarah Roudhotul Aulia; Abni Widya Dewi; Muselvia Nurcahyani; Shalsabella Dewi Setyaning Tyas; Angga July Setiawan; Alvina Hasna Mufidah Ariadna; Regina Masli; Hafidha Asni Akmalia (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study discusses the implementation of an anti-bullying socialization program at SDN Karangtengah, located in Karangtengah Village, Kaliwungu Subdistrict, Kendal Regency. The program aimed to raise awareness about the dangers of bullying, its forms, and prevention strategies among students. Conducted over five days, it employed interactive methods such as lectures, group discussions, role-playing, and poster-making to engage students and enhance their understanding of bullying. The program successfully increased students' awareness and willingness to report bullying incidents, contributing to a safer school environment. Key factors supporting the program's success included active participation from the school administration, teachers, and community members. However, challenges such as limited time, resource constraints, and varying levels of understanding highlighted the need for ongoing support and extended program duration. The study recommends enhancing teacher training, integrating anti-bullying education into the curriculum, and fostering greater community involvement to ensure the program's long-term impact. This approach will help maintain a culture of safety and respect at SDN Karangtengah.